2012
DOI: 10.3844/ajessp.2012.622.632
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Dioxide and Volatile Organic Compound Exposure to a Community in Texas City, Texas Evaluated Using Aermod and Empirical Monitoring Data

Abstract: According to emissions data reported to the United States Environmental Protection Agency (USEPA) and the Texas Commission on Environmental Quality (TCEQ), the BP Products North America Inc. (BP) Texas City Refinery is the worst polluter of all the industries in Texas City and is one of the worst polluting refineries in the country. The facility has reported releasing substantial emissions of Sulfur Dioxide (SO2) and Volatile Organic Compounds (VOCs). Air dispersion modeling of the emissions from the facility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…PPR is concentrated within the southeastern US and emits multiple airborne pollutant classes that have been implicated in stroke pathogenesis, including PM, NO x , SO 2 , PAH, and VOCs [15][16][17]. These constituent pollutants may travel sufficient distances to expose residents of adjacent communities [17,19]. Effluent may contain hydrocarbons and related derivatives, affecting the quality of adjacent soil and potable water supplies [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PPR is concentrated within the southeastern US and emits multiple airborne pollutant classes that have been implicated in stroke pathogenesis, including PM, NO x , SO 2 , PAH, and VOCs [15][16][17]. These constituent pollutants may travel sufficient distances to expose residents of adjacent communities [17,19]. Effluent may contain hydrocarbons and related derivatives, affecting the quality of adjacent soil and potable water supplies [14].…”
Section: Discussionmentioning
confidence: 99%
“…The moderate correlation between X AQS and SO 2 at 2.5 km and 5 km buffer distances may support the use of our exposure metrics as a proxy for at least air pollution. (American Meteorological Society/ Environmental Protection Agency Regulatory Model) (AERMOD), an EPA's recommended regulatory dispersion model, revealed that SO 2 and VOCs are dispersed over 10 km in Texas City [19] and SO 2 may be coupled with air pollutants such as VOCs and particles smaller than PM 2.5 (e.g. secondary particles) close to oil refineries [17], although X AQS is less correlated with SO 2 at 10 km buffer distance in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated X ct values corresponding to 5-km buffers. This threshold was chosen based on air pollution dispersion from smokestacks of refineries and empirical correlation between petroleum production and measured levels of SO 2 , which is a byproduct of petroleum production and refining (48).…”
Section: Methodsmentioning
confidence: 99%